Biodiversity Conservation and Utilization in a Diverse World - Akeem Lameed, Gbolagade (IntechOpen, 2012)
This book "Biodiversity Conservation and Utilization in a Diverse World" sees biodiversity as management and utilization of resources in satisfying human needs in multi-sectional areas including agriculture, forestry, fisheries, wildlife and other exhaustible and inexhaustible resources. Its value is to fulfill actual human preferences and variability of life is measured by amount of genetic variation available. In viewing diversity as an ultimate moral value, one is faced with a situation in environmental preservation in order to allow components of total diversity to flourish and constitute a threat to continuous existence and decrease total diversity. The overall importance described economic benefits from bio-diversity, though difficult to measure and varying, but are limited on a local scale, increase on a regional or national scale and become potentially substantial on a transnational or global scale.